Analysis of the Influence of Leadership Style, Job Satisfaction, and Work Environment on Employee Performance in PT Kereta Api Indonesia (Persero) Regional Division I North Sumatra - Nisa Hafiza; Akhmad Taufik; Muhammad Yalzamul Insan (Formosa Journal of Social Sciences (FJSS), 2024)
The purpose of this study was to analyze the influence of leadership style, job satisfaction, and work environment on employee performance at PT Kereta Api Indonesia (Persero) Region 1, North Sumatra Province. This study also identified problems related to the relationship between leaders and employees, dissatisfaction with wages, and discomfort in the work environment. The method used is a quantitative approach with multiple linear regression analysis using SPSS version 25. Data collection techniques include sample observation and questionnaires given to 40 employees. The results of the study indicate that leadership style partially does not have a significant effect on employee performance. Job satisfaction has a positive and significant effect partially on employee performance, while the work environment has an insignificant effect partially. However, simultaneously, leadership style, job satisfaction, and work environment have a significant positive effect on employee performance